2019
DOI: 10.1186/s12879-019-4058-4
|View full text |Cite
|
Sign up to set email alerts
|

Viral suppression rate among children tested for HIV viral load at the Amhara Public Health Institute, Bahir Dar, Ethiopia

Abstract: Background Human immunodeficiency virus (HIV) infected children represent a very vulnerable population for anti-retroviral therapy (ART) drug resistance. As a global target, 90% of patients receiving ART should have HIV-RNA viral suppression. A threshold of > 1000 RNA copies/ml is used to define non-suppressed viral load. If it is confirmed in the laboratory, adherence should be addressed and should be followed by the switch to second-line ART. Therefore, the aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 12 publications
2
28
4
Order By: Relevance
“…Among children who had a recent viral load, almost one-third of children experienced virological non-suppression in their first years on ART. This corresponds with recent studies (2017-2019) from low-and middle-income countries (LMICs) (28-38%) (5,(17)(18)(19)(20)(21)(22). However, two systematic reviews (both 20%) (22,23) and other studies have found lower proportions of virological non-suppression in children, including 12% in Ethiopia (6), 18% in South Africa (15) and 20% in Thailand (24).…”
Section: Discussionsupporting
confidence: 87%
“…Among children who had a recent viral load, almost one-third of children experienced virological non-suppression in their first years on ART. This corresponds with recent studies (2017-2019) from low-and middle-income countries (LMICs) (28-38%) (5,(17)(18)(19)(20)(21)(22). However, two systematic reviews (both 20%) (22,23) and other studies have found lower proportions of virological non-suppression in children, including 12% in Ethiopia (6), 18% in South Africa (15) and 20% in Thailand (24).…”
Section: Discussionsupporting
confidence: 87%
“…Nevirapine-based regimen was significantly associated with virological and immunological failure compared to those children who were on EFV-based treatment (AOR = 1:90, (1.41-2.56), P = 0:001) or which is 2 times higher in virological and immunological failure than EFVbased treatment. Consistent findings were reported from Tanzania (AOR = 4:1, (1.6-10.4), P = 0:003) [39], Uganda [41], and Bahir Dar, Ethiopia (AOR = 1:90, 95% CI: 1.41-2.56, P = 0:001) [24]. Contrasting finding from our study was reported from Asella, Ethiopia [42] that indicated HAART regimen variability was not significantly associated Journal of Immunology Research with recovery of CD4 counts and viral load failure, Addis Ababa, Ethiopia [43] and in Uganda study [44].…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, we assessed the rate of viral load suppression, immunological response failure, and hematological abnormalities among children receiving HAART at Hawassa University ART Clinic for the reason that identification of such problems is essential to make interventions during drug and disease management among children receiving HAART for a prolonged duration of time [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors including poor adherence, age of patients, limited access to drug formulations adapted to paediatric needs, and treatment duration could be associated with VF. Also, younger age could be an additional factor related to VF in the Pediacam cohort when participants are aged less than 6 years as reported by other studies in Ethiopia and Kenya [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 68%